The New Economy and Global Stock Returns - Catao, Luis (IMF Working Papers; Working Paper, 2000)
This paper revisits the relative importance of global versus country-specific factors underlying stock returns. It constructs a new firm level data set covering emerging and developed markets and estimates a simple factor model, which breaks down stock returns into a global business cycle factor, global industry factors, country-specific factors and firm-level effects. The results indicate that the share of variation in stock returns explained by global industry factors has grown sharply since the mid-1990s, at the expense of country-specific factors. Foremost among the global factors is a 'new economy' factor, which has become a key determinant of global stock returns.